Scale‐up of a Fluidized Bed Crystallizer on the Basis of Solid Suspension. Issue 8 (9th July 2013) - Sha, Z.; Xiong, C.; Chen, Q.
Abstract The scale‐up of a fluidized bed crystallizer was studied based on solid spatial concentration distribution in the crystallizer, which was obtained with the simulation of computational fluid dynamics (CFD). The variations of solid spatial concentration distributions in the crystallizers were investigated based on different specific energy inputs. A strategy for the scale‐up of the crystallizer was suggested based on the different states of solid suspension.